MHC Class 1 and PDL-1 Status of Primary Tumor and Lymph Node Metastatic Tumor Tissue in Gastric Cancers - Ibrahim Halil Erdogdu (Gastroenterology Research and Practice)
The prognosis of metastatic gastric cancer is poor. Despite the use of VEGF-, EGFR-, and HER2-targeting agents, prognosis is still poor in advanced gastric cancer. Although cancer immunotherapy responds well in some patients, clinical use is limited due to unanswered patients. For this reason, it is necessary to know the characteristics of primary and metastatic cancer cells for patient selection for immunotherapy and additional criteria are required. MHC-1 downregulation is most frequently observed in the tumor escape mechanism of cancer cells from the immune system. MHC-1 downregulation with increased PDL-1 expression of cancer cells has an important role in immune escape. MHC-1 downregulation and PDL-1 expression have been shown in many types of cancers. However, there is no study on the status of MHC-1 and PDL-1 in primary and metastatic tumor tissue. In this study, MHC-1 and PDL-1 score in primary and metastatic tumor cells was evaluated in 43 gastric cancer patients with lymph node metastasis. According to our results, the primary tumor PDL-1 score was correlated with the number of metastatic lymph nodes (r=0.258; p=0.024) and primary tumor size (r=0.341; p=0.045). A similar correlation was found between the primary tumor PDL-1 score and the metastatic tumor PDL-1 score (r=0.213; p=0.015). In our study, MHC-1 was found to be higher in primary tumors than metastatic tumors, although not statistically significant (p=0.054). The results of our study showed high MHC-1 and low PDL-1 expression in primary tumors and low MHC-1 and high PDL-1 expression in metastatic tumors. These results reveal different biological characteristics of primary and metastatic tumor cells.